2022
DOI: 10.1073/pnas.2200230119
|View full text |Cite
|
Sign up to set email alerts
|

A brain-enriched lncRNA shields cancer cells from immune-mediated killing for metastatic colonization in the brain

Abstract: Significance Brain metastasis with current limited treatment options is a common complication in advanced cancer patients, and breast-to-brain metastasis (B2BM) is one of the major types. In this work, we report that brain metastasis oncogenic long noncoding RNA (BMOR) is a key brain-enriched long noncoding RNA for the development of B2BM. We demonstrate that BMOR allows B2BM cells to colonize the brain tissue by evading immune-mediated killing in the brain microenvironment. At the molecular level, B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Brain parenchyma limits cancer cell invasion and survival through the protein plasmin, that DTCs counteract by secreting serpin proteins to initiate their colonization ( 155 ). The lncRNA BMOR has also been reported to promote breast cancer cell brain colonization, possibly through evasion of immune clearance ( 159 ). Two recent reports have addressed the role of dormancy in this process.…”
Section: Station 3: At the Metastatic Niche The Final Stage On The Roadmentioning
confidence: 99%
“…Brain parenchyma limits cancer cell invasion and survival through the protein plasmin, that DTCs counteract by secreting serpin proteins to initiate their colonization ( 155 ). The lncRNA BMOR has also been reported to promote breast cancer cell brain colonization, possibly through evasion of immune clearance ( 159 ). Two recent reports have addressed the role of dormancy in this process.…”
Section: Station 3: At the Metastatic Niche The Final Stage On The Roadmentioning
confidence: 99%
“…lncRNA can regulate gene expression via chromatin modification, transcriptional, or post-transcriptional modifications and consequently impacts a variety of molecular targets . This property allows one lncRNA to have regulatory control across multiple levels, but it can be dysregulated in a tissue- and disease-specific manner. Differentiation antagonizing noncoding RNA (DANCR) is an oncogenic lncRNA overexpressed in triple negative breast cancer (TNBC), an aggressive breast cancer subtype that lacks expression of hormone receptors and suitable drug targets. DANCR is known to increase cell proliferation and invasion in TNBC. Because lncRNA is considered as an undruggable target for conventional therapeutics, RNA interference (RNAi) with small interfering RNA (siRNA) is an effective approach for regulating lncRNA for cancer therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The immune system is a highly sophisticated system that is a complex network of organs, immune cells, non-immune cells and proteins, where increasing studies have noticed essential roles of immune modulation by non-immune cells (Dainichi et al, 2021). For example, we recently reported that breast cancer cells, as non-immune cells, facilitate the formation of an immunosuppressive microenvironment via cancer-intrinsic BOMR-inhibited IRF3 (Liu et al, 2022). However, the function of GATA3 in the regulation of immunity in non-immune cells remains largely unknown.…”
Section: Discussionmentioning
confidence: 99%